Effects of three auxin-inducible LBD members on lateral root formation in Arabidopsis thaliana - Feng, Zhenhua; Zhu, Jian; Du, Xiling; Cui, Xianghuan (Planta, 2012)
In Arabidopsis, two AUXIN RESPONSE FACTORS (ARF7 and ARF19) and several Aux/IAAs regulate auxin-induced lateral root (LR) formation. As direct targets of ARF7 and ARF19, LATERAL ORGAN BOUNDARIES DOMAIN 16 (LBD16), LBD29, and LBD18 have a biological function in the formation of lateral roots (LRs). However, the details of the functions of these three LBDs have remained unclear. Each single T-DNA insert mutant has been shown to have slightly fewer LRs than the wild type. We then created a triple mutant, which exhibited a dramatic defect in the LR formation. Our results show that the Ibd mutations can lead to impairment in auxininduced pericycle cell division and in the expression levels of some D-type cyclins (CYCDs). Simultaneously, PLETHORA (PLT) and PIN-FORMED (PIN), which have been well documented to promote cell mitotic activity and are required for auxin response effects, were down-regulated by these Ibd mutations. Our results so far indicate that CYCDs, PLT, and PINs are the main targets of the LBDs. We believe that these three LBDs are involved in cell cycle progression of the pericycle in response to auxin. Overexpression of any of these three LBD genes in the triple mutant was found incapable of completely replacing the other two LBDs. The phenotypes of Ibd29 mutants were not completely consistent with Ibdl6 or Ibd18 mutants. This indicates that LBD29 may play a distinctive role compared with LBD 16 or LBD 18 and LBDs might play partially independent roles during the formation of LRs.